Ćuk topology based single phase AC-DC converter wih low THD and high power factor - Kabir, Md Ashfanoor; Abedin, Amina Hasan; Islam, Samia; Choudhury, Mohammad Ali A Shoukat (© 2011 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 37th Annual Conference of the IEEE Industrial Electronics Society, IECON 2011; Melbourne, VIC; Australia; 7 November 2011 through 10 November 2011 [© 2011 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/IECON.2011.6119489